(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Since children who read multicultural literature can both see themselves reflected in the literature they read and be exposed to authors from diverse backgrounds who can serve as role models for them, there has long been a call in the United States for more diverse representation in children’s and adolescent literature.